Psychometric Properties of the Persian Version of the Parenting Competence Scale - Rahimi, Reza; Khodaei, Ali (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to investigate the psychometric properties of the Parenting Competence Scale.Methods: This research was a descriptive survey. The statistical population included all male and female students in the first grade of high school in District 11 of Tehran during the 2022-2023 academic year. Participants were selected using a convenience sampling method. In this study, to examine the psychometric properties of the Parenting Competence Scale, confirmatory factor analysis was used for construct validity, correlation coefficients for convergent validity, and internal consistency coefficients for reliability. For this purpose, 350 adolescents aged 13 to 15 responded to the Parenting Competence Scale, the Strength-based Parenting Scale (Jach et al., 2018), and the Engagement, Perseverance, Optimism, Connectedness, and Happiness Instrument for Adolescent Well-being (Kern et al., 2016).Findings: The results of confirmatory factor analysis indicated that the Parenting Competence Scale, with a structure comprising four factors—parental warmth, parental demand, social value of patience, and social value of respect for privacy—had good construct validity. Additionally, the results related to the correlation between the dimensions of parenting competence with strength-based parenting and adolescent well-being supported the convergent validity of the Persian version of the Parenting Competence Scale. Furthermore, the internal consistency coefficients of the subscales of privacy, patience, parental warmth, and parental demand were 0.86, 0.79, 0.80, and 0.78, respectively, defending the reliability of the Persian version of the aforementioned scale.Conclusion: Overall, the results of this study, while defending the conceptual positions derived from a positive and non-deficit approach to the field of parenting studies on which the conceptual foundation of the idea of parenting competence is based, also provided substantial evidence in support of the technical characteristics of the validity and reliability of the Persian version of the Parenting Competence Scale.